Congenital central hypoventilation syndrome and Hirschsprung's disease in half sibs. Issue 4 (April 1989) - Hamilton, J; Bodurtha, J N
Abstract : We report two infants with congenital central hypoventilation syndrome and Hirschsprung's disease who have the same father but different mothers. The genetic implications of these cases are discussed.